Antropometry of mutuality's field in language and speech - V K Radzikhovskaya (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2012)
This report represents the functional semantic mutuality's category within framework of the antropometry as the system of measurings (assesses) into the space of mutuality's relations.